Hepatic Carcinoma-Associated Fibroblasts Promote an Adaptative Response in Colorectal Cancer Cells That Inhibit Proliferation and Apoptosis: Nonresistant Cells Die by Nonapoptotic Cell Death - Berdiel-Acer, Mireia (Neoplasia Press Inc., 2011)
Carcinoma-associated fibroblasts (CAFs) are important contributors of microenvironment in determining the tumor's fate. This study aimed to compare the influence of liver microenvironment and primary tumor microenvironment on the behavior of colorectal carcinoma. Conditioned medium (CM) from normal colonic fibroblasts (NCFs), CAFs from primary tumor (CAF-PT) or liver metastasis (CAF-LM) were obtained. We performed functional assays to test the influence of each CM on colorectal cell lines. Microarray and gene set enrichment analysis (GSEA) were performed in DLD1 cells cultured in matched CM. In DLD1 cells, CAF-LM CM compared with CAF-PT CM and NCF led to a more aggressive phenotype, induced the features of an epithelial-to-mesenchymal transition more efficiently, and stimulated migration and invasion to a greater extent. Sustained stimulation with CAF-LM CM evoked a transient G(2)/M cell cycle arrest accompanied by a reduction of apoptosis, inhibition of proliferation, and decreased viability of SW1116, SW620, SW480, DLD1, HT-29, and Caco-2 cells and provoked nonapoptotic cell death in those cells carrying KRAS mutations. Cells resistant to CAF-LM CM completely changed their morphology in an extracellular signal-regulated protein kinase-dependent process and depicted an increased stemness capacity alongside the Wnt pathway stimulation. The transcriptomic profile of DLD1 cells treated with CAF-LM CM was associated with Wnt and mitogen-activated protein kinase pathways activation in GSEA. Therefore, the liver microenvironment induces more efficiently the aggressiveness of colorectal cancer cells than other matched microenvironments do but secondarily evokes cell death. Resistant cells displayed higher stemness capacity.